RANCANG BANGUN ALAT PENGGERAK LAMPU INFRA MERAH SECARA UP-DOWN DILENGKAPI SENSOR JARAK - Salman Salman; Yulizham Yulizham (JURNAL MUTIARA ELEKTROMEDIK, 2019)
Of the advances that have had a positive impact on the development of health equipment, one of which is an infrared therapy device. Infrared therapy is one of the tools in the field of physiotherapy that is used to improve blood circulation, helping to reduce muscle aches, muscle aches, shoulder or joint stiffness, etc. This tool is used to determine the safe distance of infrared radiation exposure and Up-down movement for a more even therapeutic process. Infrared therapy uses the HC-SR04 Ultrasonic sensor to determine the distance and drive of a DC motor. Users can simply adjust the sitting position with a distance of 45 cm to 60 cm, the lights will turn on with the specified time. This tool will work if the distance of the patient includes a distance of 45 cm to 60 cm, if the distance is below 45 cm and above 60 cm the infrared light will not turn on and the motor will turn off because the safe distance of exposure is 45 cm - 60 cm. -down according to the list of programs created. The distance display can be seen on the LCD display. The advantage of this tool is that it can determine the safe distance of infrared therapy light and up and down movements.